PENGARUH PERMAINAN PUZZLE DAN METODE DISKUSI TERHADAP PENGETAHUAN DAN SIKAP ANAK USIA DINI (5-6 TAHUN) MENGENAI SEKSUALITAS (STUDI DI TK KELURAHAN BUGANGAN, SEMARANG TIMUR, KOTA SEMARANG) - Hasna Fadhilah Muflihah; Zahroh Shaluhiyah; Priyadi Nugraha Prabamurti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
The city of Semarang, which was named the Eligible City of Children in Indonesia, still has sexual violence against children case. From 16 sub-districts in Semarang City, East Semarang District is the sub-district that has the highest cases of sexual violence with cases that occur every year in Bugangan Village. The lack of sexuality information in children is one reason of children become sexual violence victims. Sexuality information can be delivered in many ways to children, for example puzzle. This study aims to determine the effect of puzzle and discussion methods on early childhood knowledge and attitudes about sexuality. The type of research is a quasi experiment design with a non equivalent control group research design. The sampling technique used purposive sampling with a total of 20 respondents for each group. Data analysis was carried out by univariate and bivariate. The results showed there was an increase in knowledge and attitudes by 40% after being given intervention in the experimental group, while in the knowledge control group and attitudes tended to remain. The results of bivariate analysis state that puzzle and discussion methods can affect children's knowledge (???? = 0,000) and children's attitudes (???? = 0,000) in the experimental group, while in the control group the children's knowledge is (???? = 0,096) and children's attitudes (???? = 0,666 ) shows there is no difference between pretest and posttest.